Effectiveness Test of Ketapang Leaf Ethanol Extract (Terminalia catappa L.) with TWEEN and PEG Diluents on the Mortality of Aedes aegypti Larvae - Azmi, Aninditha Syavela; Nurhayani, Nurhayani; Bestari, Rochmadina Suci; Sintowati, Retno (Jurnal Ilmu Kesehatan, 2023)
Diseases caused by Aedes aegypti mosquitoes can be controlled with vectors in the form of larvicide administration, but if it is excessive, it causes environmental pollution and causes larval resistance so that natural larvicides are needed. Ketapang leaves are tested to determine the effectiveness of larvicides against Aedes aegypti larvae. To determine the effectiveness of the ethanol extract of ketapang leaves (Terminalia catappa L.) with TWEEN dilution on the mortality of Aedes aegypti larvae. The research is experimental with the research design used is posttest only controlled group design. This design compares the experimental group with the control group. The groups used were groups K (+) and K (-), and the TWEEN/PEG treatment group which contained ketapang leaf extract with a concentration of 1,5% and 2%, respectively. The sample of Aedes aegypti larvae used was instar III IV. Normality, Kruskal-Wallis, Mann-Whitney and Probit tests are used for data processing. Mortality was highest with his PEG treatment at 1,5% and lowest with TWEEN at 2%. The effect of ethanol extract from ketapang leaves (Terminalia catappa L.) with TWEEN diluent was the same as PEG on the mortality of Aedes aegypti larvae. The ethanol extract of ketapang leaves (Terminalia catappa L.) with dilutions of TWEEN and PEG was less effective than abate.